A novel spectral-splitting solar indoor lighting system with reflective direct-absorption cavity: Optical and thermal performance investigating. (15th August 2022) - Ji, Yaning; Yuan, Yu; Wu, Gang; Feng, Chaoqing; Cheng, Ruifeng; Ma, Qianlei; Chen, Xinge; Tong, Yuxin
Highlights: A novel full spectrum utilization solar indoor lighting system for Plant Factory was investigate. The spectrum splitting mirrors integrated with water can perfectly separate sunlight desirable. A reflective direct-absorption cavity was used to absorb non-visible light energy and cool fibers. The solar energy utilization efficiency of the device can reach 50%. The temperature of the coupling focus of the fiber was maintained at 27–37 °C. Abstract: Sunlight contains a wide range of the spectrum, and the spectrum used for plant photosynthesis is mainly located in the visible band (380–780 nm), while the spectral energy of other bands is not suitable for plant growth because it generates heat in summer. In this paper, a novel spectral-splitting solar indoor lighting system with a reflective direct-absorption cavity for Plant Factory was developed, which used the combination of pure water and spectrum splitting mirrors to perfectly separate the visible light and non-visible light of sunlight. Visible light was conducted to Plant Factory by optical fiber to provide illumination for plants, and non-visible light was trapped and then absorbed by a reflective direct-absorption cavity and convert into thermal energy. The structural parameters of the reflective direct-absorption cavity were optimized based on the Monte Carlo method, and the light conduction and heat transfer models were established to analyze the photo-thermal performance of the device. The results of indoor and outdoor tests showed that the solar energy utilization efficiency of the device could reach 50%, among which the light transmission efficiency and heat collection efficiency were 24.7% and 25.3%, respectively. The temperature of the optical fiber coupling end face was kept in the range of 27–37 °C, which can ensure the safe and efficient operation of the optical fiber. It provides a new idea for the protection of optical fiber, the efficiency improvement of sunlight conduction lighting technologies, and the energy saving of the Plant Factory lighting in the future.